Evaluación de la calidad de la carne de cerdo postmortem en el Camal Municipal de Alamor - Maza Merchan, Jonathan Leandro (2023)
Pig meat is considered an essential nutrient form of alimentation this nutrient has many requirements necessary for assuring alimentary security, there are many factors such as the antemortem that will have negative effects in the postmortem. This research evaluated with PH and color of pig’s meat for 45 minutes and 7 hours postmortem in the Alamor Municipal Camal, moreover was used a PH metro of mark Hanna Instrument “Food Care Meat Taster” to determine the PH and a card of color scale called “Pork Quality Standards” for determinate the meant color. As a result, it will identify that at 45 minutes 28% of meats pertinent a PSE (Palide suave and exudative) as values of the normal range (6,4) afterward to 7 hours will identifications that 26% represent 05 meat DFD (dark, firms and hard) as values of PH 6,00-6,33. The meant color will appreciate that 45 minutes of 14% represent weak colors and 7 hours the 26% dark colors. In conclusion, there are meats DFD in the Alamor Municipal Camal as a recommendation ought to realize meditation of PH to verification the performance of muscle maturation meat to restore Ph values